Macro-Micro Study on Mechanical Properties of Frozen Fine Sandstone Based on DEM Mathematical Model - Maoyan Ma; Min You; Shuguang Peng; Biao Zhang; Yuan Lin (Journal of Function Spaces)
The study of freezing rock mechanical properties is getting more and more urgent because of coal mine construction in western China. Particle discrete element method (DEM) can describe discontinuous medium problem mathematically. In order to reveal the mechanical failure mechanism of frozen fine sandstone, the uniaxial compressive strength test of frozen fine sandstone was carried out, and then, DEM was used to simulate the uniaxial test of frozen fine sandstone. Furthermore, the nuclear magnetic resonance (NMR) technology was used to obtain pore distribution of the freezing sandstone. Finally, the results of NMR test and discrete element simulation were combined to reveal the microscopic mechanism of mechanical change in freezing fine sandstone. The DEM results show that the strength of frozen fine sandstone increases with the decrease of temperature. With the decrease of temperatures, strain softening occurs in frozen sandstone, which indicates that the discrete element simulation results are in good agreement with the uniaxial test results. Therefore, DEM can be used to simulate the mechanical behavior of frozen fine sandstone. At the same time, the DEM results also indicate that the formation and development of the shear band are the precursor of the failure of the sample. Furthermore, the NMR test confirms that temperature has a great impact on the pore distribution of sandstone. With the decrease of temperature, the pore ice content increases greatly, which induces a great decrease in NMR porosity and a vast decrease in the proportion of large and medium pores in all pores. Meanwhile, with the growth of the cohesion induced by increasing ice content, the uniaxial compressive strength increases macroscopically.